Evaluación del ciclo reproductivo de la rana marsupial andina (gastrotheca riobambae) en jaulas exteriores en el Centro Experimental Académico Salache, Universidad Técnica de Cotopaxi - Pacheco Castellanos, Paola Gabriela (2015)
The research conducted at the Experimental Academic Center Salache (CEASA) about different aspects of the Andean marsupial frog (Gastrotheca riobambae) reproductive cycle; as well as, their behavior in semi-captivity, it means, outdoor enclosures allowed to experiment with own amphibians climatic conditions in their free lives, but in a controlled environment space. Direct observation as a technique for data collection was used, without the need for intervention by the researcher. The researcher could observe that the behaviour of Gastrotheca riobambae is similar to many other frogs: with crepuscular and nocturnal habits; nevertheless, they showed activity during the day because several individuals were found napping in areas where they could receive sun; additionally they showed higher activity during the rainy season....